PERBEDAAN KEMAMPUAN BERPIKIR KRITIS SISWA MENGGUNAKAN PBL BERBANTUAN MIND MAPPING DENGAN PBL BERBANTUAN PPT - Lestari, Indah; Sukidin, Sukidin; Herlindawati, Dwi (STKIP Persada Khatulistiwa Sintang, 2026)
The low critical thinking ability of students is the basis for this study. The focus of this study is to compare the critical thinking ability of class X students of SMAN Jenggawah in economics learning with the implementation of the PBL model assisted by Mind Mapping and the PBL model assisted by PowerPoint (PPT). This study applies a quasi-experimental method with a posttest nonequivalent control group design. This study involved all class X students of SMAN Jenggawah as the population, the research sample was selected using the purposive sampling method. Primary data were obtained from posttests, observations, and interviews. Hypothesis testing was carried out through independent sample t-tests. The results showed that the average value in the class using the PBL model assisted by Mind Mapping was higher, which was 80.14 compared to the class implementing the PBL model assisted by PPT of 74.29. Thus, it can be concluded that the PBL model supported by Mind Mapping has a significant effect on critical thinking skills.